Mesiodens and upper central incisors retained with root dwarfism and dilacerated root. Clinical case report - Mora Ramírez, María del Cisne (2023)
Mesiodens are a type of supernumerary tooth that appears more frequently in the definitive dentition, they are pieces generally located in the midline of the upper jaw, of unknown etiology, but the most accepted theory is due to a hyperactivity of the dental lamina during morphogenesis. The purpose of this work is to describe the case of a 14-year-old male patient with no relevant pathological history. The intraoral clinical analysis shows a dental organ in the midline of the upper jaw compatible with a mesiodens and another included located at the level of the nasal cavity. On tomographic analysis there is presence of a hyperdense area between upper incisors with a characteristic compatible with a mesiodens, in a sagittal section a hyperdense area is observed 7mm from the alveolar rim towards the floor of the nostrils, an inverted dental structure with a diameter of 8mm, ectopic location. An aspect of root dwarfism can be seen in the included upper central incisors that are not favorable for the patient.